Normal-Weight Central Obesity: Implications for Total and Cardiovascular Mortality - Sahakyan, Karine R; Somers, Virend K; Rodriguez-Escudero, Juan P; Hodge, David O; Carter, Rickey E; Sochor, Ondrej; Coutinho, Thais; Jensen, Michael D; Roger, Véronique L; Singh, Prachi; Lopez-Jimenez, Francisco (Annals of internal medicine, 2015)
The relationship between central obesity and survival in community-dwelling adults with normal body mass index (BMI) is not well-known. To examine total and cardiovascular mortality risks associated with central obesity and normal BMI. Stratified multistage probability design. NHANES III (Third National Health and Nutrition Examination Survey). 15,184 adults (52.3% women) aged 18 to 90 years. Multivariable Cox proportional hazards models were used to evaluate the relationship of obesity patterns defined by BMI and waist-to-hip ratio (WHR) and total and cardiovascular mortality risk after adjustment for confounding factors. Persons with normal-weight central obesity had the worst long-term survival. For example, a man with a normal BMI (22 kg/m2) and central obesity had greater total mortality risk than one with similar BMI but no central obesity (hazard ratio [HR], 1.87 [95% CI, 1.53 to 2.29]), and this man had twice the mortality risk of participants who were overweight or obese according to BMI only (HR, 2.24 [CI, 1.52 to 3.32] and 2.42 [CI, 1.30 to 4.53], respectively). Women with normal-weight central obesity also had a higher mortality risk than those with similar BMI but no central obesity (HR, 1.48 [CI, 1.35 to 1.62]) and those who were obese according to BMI only (HR, 1.32 [CI, 1.15 to 1.51]). Expected survival estimates were consistently lower for those with central obesity when age and BMI were controlled for. Body fat distribution was assessed based on anthropometric indicators alone. Information on comorbidities was collected by self-report. Normal-weight central obesity defined by WHR is associated with higher mortality than BMI-defined obesity, particularly in the absence of central fat distribution. National Institutes of Health, American Heart Association, European Regional Development Fund, and Czech Ministry of Health.